The Implementasi Algoritma Kriptografi AES-128 (RIJNDAEL) Untuk Keamanan Informasi Dokumen Rahasia PT. PLN (PERSERO) UP2B Sistem Minahasa - Merlin Aprilia Liow; Gladly Caren Rorimpandey; Alfiansyah Hasibuan (Riset Sinergi Indonesia (RISINDO), 2026)
The rapid advancement of digital technologies in the electricity sector has increased the demand for stronger information security systems, particularly in managing confidential documents that support operational decision-making. PT PLN (Persero) UP2B Sistem Minahasa serves as a critical unit responsible for regulating and monitoring electrical load distribution in North Sulawesi, making the protection of internal documents essential to maintaining operational integrity and confidentiality. However, the current document management process still relies on conventional methods and lacks the support of modern encryption technologies, leaving sensitive data vulnerable to unauthorized access, information leakage, and misuse. These risks became more evident following several data breach incidents reported in 2022 and 2023. This research focuses on developing a digital document security system utilizing the Advanced Encryption Standard (AES-128) algorithm to protect files in PDF, DOCX, XLS, and TXT formats. The research stages include requirement analysis, system design, implementation using PHP, MySQL, and OpenSSL, and performance testing for the encryption and decryption processes. The results indicate that AES-128 efficiently encrypts documents and produces files that cannot be accessed without a valid key, while the decryption process successfully restores the original content with an accuracy level of up to 90%. Overall, the implementation of this system significantly improves document security within UP2B Sistem Minahasa and can serve as a reference for strengthening information security policies across PLN units.